Initial and mid-term results of LEO Baby stent-assisted coiling of intracranial aneurysms located in small arteries: A single-center experience with 131 consecutive patients - Shen, Yunan; Ni, Heng; Li, Jingfeng; Jia, Zhenyu; Cao, Yuezhou; Shi, Haibin; Zhao, Linbo; Liu, Sheng (Frontiers in Neurology, 2022)
Background and purpose Low-profile intracranial stents such as the LEO Baby stents are considered to be advantageous for the treatment of intracranial aneurysms originating from small arteries. This study aimed to evaluate the initial and mid-term clinical and angiographic results of LEO Baby stents in stent-assisted coiling of intracranial aneurysms with small parent arteries (<2.5 mm). Methods We performed a retrospective study to identify 131 patients with aneurysms arising from small parent arteries treated with Leo Baby stent-assisted coiling in a single institution between October 2018 and June 2021. We assessed the immediate and progressive aneurysm occlusion rates, procedure-related complications, and clinical outcomes. Results A total of 131 patients with 135 aneurysms were identified, including 65 (48.1%) cases of acutely ruptured aneurysms. Technical success was achieved in all cases (100%). The immediate angiography showed complete occlusion in 111 aneurysms (82.2%), neck remnants in 19 (14.1%), and residual sac in 5 (3.7%). Procedure-related complications occurred in 14 cases (10.3%), including 13 (9.6%) thromboembolic complications and 1 (0.7%) hemorrhagic complication. Six-month follow-up angiography was achieved in 106 (78.5%) aneurysms, which showed complete occlusion in 102 (96.2%) aneurysms, neck remnants in 2 (1.9%), and residual sac in 2 (1.9%). Clinical follow-up was available in all patients with a median duration of 6.8 months, and favorable clinical outcomes (modified Rankin Scale score: 0–2) reached 91.6%. The mortality rate was 4.6%. Conclusion Our results demonstrate that stent-assisted coiling of intracranial aneurysms located on small arteries using LEO Baby stents is technically feasible, highly effective, and has midterm durability in aneurysmal occlusion.